Share The Formula You Found

+Label +Description

Recently Referred Formulae

p_{[a-*-*]}=p_a+\sum_{n\neq a} p_n frac{p_a}{1-p_n}+sum_{n\neq m,a}sum_{m\neq a} p_mfrac{p_n}{1-p_m}frac{p_a}{1-p_m-p_n}
p_{[a-*-*]}=p_a+\sum_{n\neq a} p_n frac{p_a}{1-p_n}+sum_{n\neq m,a}sum_{mneq a} p_mfrac{p_n}{1-p_m}frac{p_a}{1-p_m-p_n}
p_{[a-*-*]}=p_a+\sum_{n\neq a} p_n frac{p_a}{1-p_n}+sum_{nneq m,a}sum_{mneq a} p_mfrac{p_n}{1-p_m}frac{p_a}{1-p_m-p_n}
p_{[a-*-*]}=p_a+\sum_{nneq a} p_n frac{p_a}{1-p_n}+sum_{nneq m,a}sum_{mneq a} p_mfrac{p_n}{1-p_m}frac{p_a}{1-p_m-p_n}
\sum_{nneq a} p_n\frac{p_a}{1-p_n}=p_b\frac{p_a}{1-p_b}+p_c\frac{p_a}{1-p_c}+p_d\frac{p_a}{1-p_d}+p_efrac{p_a}{1-p_e}